Meningsfulla möten? : om integration i utemiljön - Lindberg, Stefan (SLU/Landscape Architecture (until 121231), 2010)
Integration policies have failed to make diversity into anything more than occupying the same physical space. People of different cultural background still do not share their lives to any real extent. Attempts made within planning and landscape architecture to catalyst the integration process have mainly been focused on structural measures, such as residential policies. As for outdoor environments, non-verbal casual encounters in the shape of crossing paths are assumed to lie at the heart of urban social integration.